(3GdOQGeG GdJdjaRjhfjI h CKQgG aj MjGI CWaGdfG (B/s - (3GdMSjfj, CeGfj YeQs ((3GdbGgQI (B:s (3YGde GdcJH ,s, 2005)
(3jJVef gPG GdcJGH fXQjJjf ef Gge fXQjGJ GdEYdGe h ef GcKQ GdGHhGH GdTGFYI aj gPG GdcJGH gh aUd fXQj Yf OhQ GdJdjaRjhf aj GdJfTFI GdGLJeGYjI ddCWaGd h gj YedjI MjhjI aj MjGI LejY GdHTQ h QcR GdcJGH Ydi GcJSGH GdWad ddeYQaI h GdSdhc h GdJcja GdGLJeGYj aj TJi eLGdGJ GdMjGI (B.s
(3HHdjhZQGajG (B: (3U(B.196-176s
Keywords: (3GdJdaRjhfs; (3GdJdjaRjhfs; (3GdSeYj GdHUQjs; (3GdEYdGes